Research Agenda for Computer Science Education - Ashfaq Gul Daoud (Spectrum of Engineering Sciences, 2024)
This study investigates the extent and comprehensiveness of research on computer science education (CSE). Initially, we in order to distinguish CSE research from other forms of educational research, it is imperative to clearly define its objectives andshowcase its distinctiveness as a field of study. When evaluating the current state of CSE research, we strive to categorize past discoveries into overarching themes, considering the diverse advancements that have been implemented in the field over time. In addition, we assess each category by taking into account the prospectivebenefits and drawbacks. On the contrary, we argue that past investigations haveoverlooked educational theory. Consequently, teachers lack the "pedagogical content knowledge" required to comprehensively grasp the cognitive and instructional challenges that students encounter while learning. Finally, we emphasize the keytopics that warrant more investigation in future research on computer scienceeducation (CSE). Keywords: POP-I.B. programmer education POP-V.B. literature reviewPOP-VI.D. Computer Science Education Research